How to measure political gnosis? Empirical evidence from Putin’s Russia - Rak, Joanna (Przegląd Politologiczny, 2017)
The research applies a method of sources analysis that draws upon a qualitative comparative study of three speeches delivered by Russia’s President Vladimir Putin during his annual news conferences. It aims to solve the problems: how was political gnosis changing in Putin’s statements over the subsequent 2014–2016 meetings? And how was Putin triggering off a performative potential of presumably non-gnostic elements of discourse to enhance political gnosis? It identifies the drift from authoritarian to totalitarian and democratic gnosis and recognizes a moderate extent of the intensity of political gnosis. The article contributes to political sociology by creating and testing the empirical effectiveness of a research tool for measuring the types and intensity of political gnosis, and distinguishing between political diagnosis and gnosis.